Adjusting Words to Music: Prolongating Syllables and the Example of 'Dactylo-Epitrite'. (2018) - Hagel, Stefan
Abstract: Comparison between an original ancient composition and modern supplements shows that the ancient poetcomposer paid attention to sub-metrical parameters defining the suitability of a metrically long syllable for extended voiced performance. This criterion is explored as a potential guide to overlong syllables, developing a statistical method including thoroughly calculated weighted expectations. The method is then applied to Pindar's dactylo-epitritic Epinicia, where the rhythmical time of 'missing link syllables' is shown to have been incorporated within the preceding syllable. The notation and the rhythm of dactylo-epitrites are discussed in detail.